Factores que afectan la relación anteroposterior de los maxilares: posición anteroposterior del punto nasion, altura facial, altura dentaria e inclinación del plano oclusal - Marín-P., Harold; Zuluaga-V., Catalina; Cortés-Castaño, Nelson; Hernández-S., Napoleón (Revista Facultad de Odontología Universidad de Antioquia, 2017)
The analysis of sagital jaw relationship is important in orthodontic diagnosis and treatment planning, and can be investigated by angular and linear parameters. The ANB angle has been used to evaluate such relationship but it does not provide an adequate assessment of the skeletal discrepancy between the jaws in the sagital plane, attempts have been made in order to replace it. In the present study it was used a mathematic formula derived by Hussels and Nanda (1984), to evaluate factors affecting the ANB angle. This method was applied to 77 patients by a designed digital cephalometric system. The patients were classified in skeletal jew relationship as class I, 11, III and con-elation coefficients showed that the measured ANB angle and the calculated angle by the formula are significantly con-elated (r = .99), suggesting that both methods can be used. However, patient classification ranges showed big differences. Furthermore, the validity of a new angle Nasion-Condileon-Oclusal (NCO), was evaluated to observe the behavior of the occlusal plane respect to Nasion-Condileon plane ( N-C), existing some degree of correlation with Nasion-Silla-Oclusal angle (NSQ); therefore, the proposed angle NCO, allows to assess the inclination of the occlusal plane with the facial height.